2014
DOI: 10.1212/wnl.0000000000000966
|View full text |Cite
|
Sign up to set email alerts
|

HSJ1 -related hereditary neuropathies

Abstract: Taken together, in our cohort of 90 probands, we confirm that HSJ1 mutations are a rare but detectable cause of autosomal recessive dHMN and CMT2. We provide clinical and functional information on an HSJ1 splice-site mutation and report the detailed phenotype of 2 patients with CMT2, broadening the phenotypic spectrum of HSJ1-related neuropathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 36 publications
1
43
0
Order By: Relevance
“…In 2012, Blumen et al reported mutations in HSJ1 in a consanguineous Moroccan family with dHMN [48]. Recently, a second mutation was identified in a Turkish family also with dHMN [49]. Both mutations are homozygous and are located at donor splice sites, leading to the loss of HSJ1 protein expression.…”
Section: Hsj1 (Dnajb2)mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, Blumen et al reported mutations in HSJ1 in a consanguineous Moroccan family with dHMN [48]. Recently, a second mutation was identified in a Turkish family also with dHMN [49]. Both mutations are homozygous and are located at donor splice sites, leading to the loss of HSJ1 protein expression.…”
Section: Hsj1 (Dnajb2)mentioning
confidence: 99%
“…Both mutations are homozygous and are located at donor splice sites, leading to the loss of HSJ1 protein expression. A third mutation in HSJ1 has also been identified recently, this time in a family with Charcot-Marie-Tooth type 2 (CMT2) [49]. CMT2 closely resembles dHMN but patients have sensory abnormalities in addition to motor involvement.…”
Section: Hsj1 (Dnajb2)mentioning
confidence: 99%
“…In this case, the expression of DNAJB2 was dampened in fibroblasts from the patients and overexpression of the protein reduced the formation of inclusions in a neuronal cellular model, suggesting DNAJB2 is active in motor neurons and/or muscle (Blumen et al, 2012). Two additional homozygous mutations were later described in the DNAJB2 gene, c.229+1G>A and c.14A>G (p.Y5C), in a family diagnosed with dHMN (dHMN5) and another with CMT2 (CMT2T), respectively (Gess et al, 2014). More recently, a homozygous large deletion was reported in a family with spinal muscular atrophy and parkinsonism, broadening the clinical spectrum of DNAJB2 related neuropathies (Sanchez et al, 2016).…”
Section: The Growing List Of Chaperones Involved In Distal Hereditarymentioning
confidence: 99%
“…1 Since then, two other families with different HSJ1 mutations have been described: one with a dHMN phenotype and the other with a Charcot-Marie-Tooth disease type 2 (CMT2) phenotype. 2 We identified the HSJ1 c.352+1G>A mutation in 10 patients who underwent long-lasting follow-up. We describe their phenotype and clinical evolution.…”
Section: Introductionmentioning
confidence: 97%